2019
DOI: 10.1371/journal.pone.0219784
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic oxytocin receptor-expressing neurons in the preoptic area of the mouse brain

Abstract: Oxytocin is involved in the regulation of social behaviors including parental behaviors in a variety of species. Oxytocin triggers social behaviors by binding to oxytocin receptors (OXTRs) in various parts of the brain. OXTRs are present in the preoptic area (POA) where hormone-sensitive sexually dimorphic nuclei exist. The present study was conducted to examine whether sex differences exist in the distribution of neurons expressing OXTRs in the POA. Using OXTR-Venus (an enhanced variant of yellow fluorescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 77 publications
2
32
0
Order By: Relevance
“…In contrast, the hypothalamic area showed a continuous increase into adulthood with sexually dimorphic expression of OTR in the PMv and AVPV, parts of the hypothalamic behavioral control column that generates sexually motivated behavior 38 . This suggests that OTR in hypothalamic nuclei plays a role in generating sex-specific behavior during sexual maturation 36,44,61 .…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the hypothalamic area showed a continuous increase into adulthood with sexually dimorphic expression of OTR in the PMv and AVPV, parts of the hypothalamic behavioral control column that generates sexually motivated behavior 38 . This suggests that OTR in hypothalamic nuclei plays a role in generating sex-specific behavior during sexual maturation 36,44,61 .…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the anteroventral periventricular nucleus (AVPV) near the medial preoptic area showed higher OTR expression in females than males at P56, but not before (Figure 7B). A recent study identified abundant estrogen-dependent OTR expressing cells in the AVPV, co-expressing estrogen receptor in female mice 36 . This result suggests a potential role of OTR in sexual behavior 36–38 .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study identified abundant estrogen-dependent OTR expressing cells in the AVPV, co-expressing estrogen receptor in female mice 36 . This result suggests a potential role of OTR in sexual behavior 36–38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OT is released in the paraventricular nucleus and supraoptic nucleus of the hypothalamus in the brain and also implicated in regulating the social behaviors besides mating, maternal behavior, attachment, aggression, and sexual behavior. Recent studies have demonstrated that OT produces anxiolytic, antidepressant, and pro-social effects in animal models ( Ferguson et al, 2001 ; Heinrichs et al, 2003 ; Sharma et al, 2019 ). Due to its functions on the improvement of social recognition, the intranasal administration of OT has been under clinical studies for the treatment of ASD characterized by social deficits in adults and juveniles ( Anagnostou et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%